Counter hegemony, popular education, and resistances: A systematic literature review on the squatters’ movement - Ballesteros-Quilez, Julia; Rivera-Vargas, Pablo; Jacovkis, Judith (Frontiers in Psychology, 2022)
The squatting movement is a social movement that seeks to use unoccupied land or temporarily or permanently abandoned buildings as farmland, housing, meeting places, or centers for social and cultural purposes. Its main motivation is to denounce and at the same time respond to the economic difficulties that activists believe exist to realize the right to housing. Much of what we know about this movement comes from the informational and journalistic literature generated by actors that are close or even belong to the movement. However, there is also a significant diversity of knowledge and scientific evidence on the squatters’ movement that is being produced by academia and that is worth knowing and grouping together. With the aim of defining and understanding how the squatters’ movement is constituted and organized, and how it acts, this research analyzes what the scientific literature affirms about it. Through qualitative research based on the systematic literature review (SLR) method, information was sought in the Web of Science (WOS) and Scopus databases. The initial universe of 262 articles was finally reduced to a sample of 32 articles. These have been analyzed by means of a categorized classification content analysis. The results obtained allow us to establish the state of the art on the squatting movement, placing special emphasis on its dynamics of resistance, its process of political subjectivation and its mechanisms of action and self-management. The study suggests that the movement is understood based on collective actions with a political role of resistance to neoliberalism and the inequalities it generates, and of response to the basic and social needs of the communities through self-management. Systematic review registration [doi: 10.5281/zenodo.7179670], identifier [7179670].